2023
DOI: 10.1209/0295-5075/ace7f2
|View full text |Cite
|
Sign up to set email alerts
|

Modified gauge-unfixing formalism and gauge symmetries in the noncommutative chiral bosons theory

Abstract: We use the gauge unfixing (GU) formalism framework in a two dimensional noncommutative chiral bosons (NCCB) model to disclose new hidden symmetries. That amounts to converting a second-class system to a first-class one without adding any extra degrees of freedom in phase space. The NCCB model has two second-class constraints -- one of them turns out as a gauge symmetry generator while the other one, considered as a gauge-fixing condition, is disregarded in the converted gauge-invariant system. We show that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 94%
“…A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 94%